2011
DOI: 10.4061/2011/392180
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Alanine-76 and Serine Phosphorylation inα-Synuclein Membrane Association and Aggregation in Yeasts

Abstract: In Parkinson's disease (PD), misfolded and aggregated α-synuclein protein accumulates in degenerating midbrain dopaminergic neurons. The amino acid alanine-76 in α-synuclein and phosphorylation at serine-87 and serine-129 are thought to regulate its aggregation and toxicity. However, their exact contributions to α-synuclein membrane association are less clear. We found that α-synuclein is indeed phosphorylated in fission yeast and budding yeast, the two models that we employed for assessing α-synuclein aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
2
21
0
2
Order By: Relevance
“…This tendency might at least partially explain the cytoplasmic inclusions detected in the cells expressing this mutant aSyn and suggest that the phosphorylation status on S129 is crucial for aggregation, in agreement with recent findings in yeast, in which S129A mutant potentiates the formation of aSyn foci [46]. GRKs and PLKs modulate the dynamics of aSyn in different ways and we did not find a consistent pattern that can explain the role of S129 phosphorylation on the distribution of aSyn.…”
Section: Discussionsupporting
confidence: 84%
“…This tendency might at least partially explain the cytoplasmic inclusions detected in the cells expressing this mutant aSyn and suggest that the phosphorylation status on S129 is crucial for aggregation, in agreement with recent findings in yeast, in which S129A mutant potentiates the formation of aSyn foci [46]. GRKs and PLKs modulate the dynamics of aSyn in different ways and we did not find a consistent pattern that can explain the role of S129 phosphorylation on the distribution of aSyn.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, S129D-␣-synuclein expressed in budding yeast exhibited decreased plasma membrane association (37). These observations are consistent with our results, suggesting the conserved mechanism of regulation of neurotoxicity and membrane binding by Ser-129 phosphorylation.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, cellular and animal studies, based on the use of the phospho-mimic strategy, reported an inhibitory effect of S129 phosphorylation on α -syn-membrane interaction. In yeast and worm models of PD, S129→A substitution (to block phosphorylation) increases α -syn membrane-bound fraction, however the phospho-mimic mutation (S129D) inhibits its association with membranes [ 46, 47 ]. A similar observation has been reported in an adeno-associated virus (AAV)-based rat genetic model of PD where immuno-electron microscopy analysis detected the majority of the non-phosphorylatable α -syn mutant (S129A) associated with cellular membranes [ 48 ].…”
Section: Introductionmentioning
confidence: 99%